Sistema ERP en HB Constructores, una propuesta para mejorar sus indicadores financieros (2020)
The proposal for the implementation of an ERP has the purpose of identifying errors that allow a continuous improvement of the financial indicators of the MS Constructora HB, also three objectives are established the first is the detailed description of the administrative processes that are executed in it MSME Constructora HB, to find shortcomings in the control of the budget of the projects being executed, the second objective is the detailed evaluation of the financial statements of the HB Construction Company to determine the weak points of the entire budget control chain in the projects and the last objective is the analysis of the ERP system that is more convenient to define a total control of the financial processes of the construction Mypime HB. Within the proposal the implementation of the ERP system was evaluated because it is the one that best defines the structural and financial processes of the mypime HB construction, determined in practice the decrease of key resources for indebtedness and integral management.